Conceptualising consumer economic nationalistic tendencies: scale development and validation - Cheah, Isaac; Phau, Ian (Routledge, 2015)
Economic nationalism has been identified as a critical component of nationalistic sentiment, influencing cognitions, attitudes, evaluation and purchase intentions. While a distinction is made between economic nationalism and other measures of national and international orientation (i.e. consumer ethnocentrism), previous empirical studies explore the concept in a ‘unified’ form. This study bridges this gap by developing a scale specifically tailored to measure consumer economic nationalistic tendencies. Scale generation, purification, validation and confirmation are achieved through four studies.